Paying for agricultural productivity - Alston, Julian M.; Pardey, Philip G.; Smith, Vincent H. (International Food Policy Research Institute, 1997)
Agricultural research and development has stimulated enormous increases in agricultural productivity in the twentieth century. Now, in response to common pressures, countries the world over are changing how they manage and pay for agricultural R&D. Paying for Agricultural Productivity reviews agricultural R&D policy in Australia, the Netherlands, New Zealand, the United Kingdom, and the United States and assesses whether the new approaches are raising or lowering the efficiency and effectiveness of R&D. To complement the case studies, the book analyzes trends in R&D investment in twenty-two developed countries. Paying for Agricultural Productivity will be an invaluable resource for economic and development specialists concerned with agricultural research and development, as well as for farmers, food processors, agricultural wholesalers and retailers, environmentalists, and research scientists.